Digital libraries : data, information, and knowledge for digital lives : 19th International Conference on Asia-Pacific Digital Libraries, ICADL 2017, Bangkok, Thailand, November 13-15, 2017, Proceedings /: data, information, and knowledge for digital lives : 19th International Conference on Asia-Pacific Digital Libraries, ICADL 2017, Bangkok, Thailand, November 13-15, 2017, Proceedings. (2017) - Unknown
No abstract available